Pengaruh Faktor Internal dan Faktor Eksternal Perusahaan Pada Kecepatan Publikasi Laporan Keuangan - Mahayani, Ni Ketut Ressa; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2019)
This research was conducted on consumer goods industry sector companies listed on the Indonesia Stock Exchange in the 2014-2017 period. Samples obtained by 16 companies with 64 observations. Profitability has a positive effect on the speed of publication of financial statements. This shows that the higher the profitability, the faster the company publishes its financial statements. The complexity of the company's operations has a negative effect on the speed of financial statement publication. This shows that the more complex the company's operations can slow the publication of its financial statements. The audit tenure and reputation of KAP have no effect on the speed of publication of financial statements. This indicates that a long or short audit tenure and reputable or non-reputable KAP have no effect on the speed of publication of financial statements. Keywords: Profitability, complexity of company operations, audit tenure, reputation of KAP, speed of publication of financial statements